Socio-cultural and Social Constructivist Theories and Its Application in EFL Classroom for Thai Pre-service Teachers: A Review for Further Research - Nithideechaiwarachok, Bussayarat; Chano, Jiraporn (Universitas Negeri Makassar, 2024)
Socio-cultural and social constructivist theories are crucial in learning and education. This article aims to inform readers about socio-cultural and social constructivist theories and to present their application in language classrooms. The body of knowledge in this article was synthesized from journal articles and books concentrating on the theories that are significant in preparing pre-service teachers in EFL classrooms. The article begins with an overview of socio-cultural theory involving mediation, activity theory, cooperative learning activities, and scaffolding. Then, the article explains the social constructivist theory and its application in EFL classrooms. The final part of the article sheds light on suggestions and future research.